The grit crust: A poly-extremotolerant microbial community from the Atacama Desert as a model for astrobiology - Jung, Patrick; Lehnert, Lukas W.; Bendix, Jörg; Lentendu, Guillaume; Grube, Martin; Alfaro, Fernando D.; Rio, Camilo del; Gutiérrez Alvarado, José Luis; van den Brink, Liesbeth; Lakatos, Michael (Frontiers in Astronomy and Space Sciences, 2022)
The grit crust is a recently discovered, novel type of biocrust made of prokaryotic cyanobacteria, 20 eukaryotic green algae, fungi, lichens and other microbes that grow around and within granitoid stone 21 pebbles of about 6 mm diameter in the Coastal Range of the Atacama Desert, Chile. The microbial 22 community is very well adapted towards the extreme conditions of the Atacama Desert, such as the 23 highest irradiation of the planet, strong temperature amplitudes and steep wet-dry cycles. It also has 24 several other striking features making this biocrust unique compared to biocrusts known from other 25 arid biomes on Earth. It has already been shown that the grit crust mediates various bio-weathering 26 activities in its natural habitat. These activities prime soil for higher organisms in a way that can be 27 envisioned as a proxy for general processes shaping even extraterrestrial landscapes. This mini-review 28 highlights the potential grit crust as a model for astrobiology in terms of colonization and 29 biotechnological applications that support human colonization of planets.